EFEKTIVITAS BAHAN AJAR MANDIRI SISWA SMA PADA MATERI SIFAT-SIFAT PERIODIK UNSUR MELALUI EMPAT TAHAP PENGOLAHAN BAHAN AJAR - Marfuah, Evi (2013)
The entitle of this study was "Effectiveness of the Self Instructional Material for High School Students in the Material Periodic Properties of the Elements Through Four Stages Processing Material". The aim of this study was to describe of instructional material processing and the effectiveness of material Periodic Properties of the Elements. The subject consisted of fifteen students of High School in Bandung. The results of this study were instructional materials of properties of the elements periodic processed through the four stages of processing which consists of instructional material selection, structuring, characterization, and reduction. Form of reduction used in the instructional material properties of elements periodic were analogy with images, tables, graphs, particularization, characterization, and reduction. The readability of instructional material was in to high category with a percentage 76%. The effectiveness of instructional material was in to high category. The effectiveness characterized by the ability of student to write main idea with a percentage 78% and the percentage of students posttest result by 71%. Processing of this instructional material should be develoved in the presence of other material in the form of textbook, hand-out, and other kinds of instructional material. Keywords : Effectiveness Instructional Material , Periodic Properties of the Elements , Four Stages Instructional Material Processing , Self Instructional Material. Penelitian ini berjudul "Efektivitas Bahan Ajar Mandiri Siswa SMA pada Materi Sifat-sifat Periodik Unsur Melalui Empat Tahap Pengolahan Bahan Ajar" dan bertujuan untuk mendeskripsikan pengolahan dan efektivitas bahan ajar sifat-sifat periodik unsur. Metode yang digunakan adalah deskriptif dengan subjek penelitian siswa dari berbagai SMA di Bandung sebanyak 15 orang. Hasil dari penelitian ini adalah bahan ajar sifat-sifat periodik unsur yang diolah melalui empat tahap pengolahan bahan ajar yang terdiri dari seleksi, strukturisasi, karakterisasi, dan reduksi. Bentuk reduksi yang digunakan pada bahan ajar sifat-sifat periodik unsur adalah analogi dengan gambar, tabel, grafik, partikularisasi, contoh, dan generalisasi. Keterbacaan bahan ajar sifat-sifat periodik unsur ini tergolong ke dalam kategori tinggi dengan persentasi 76%. Efektivitas bahan ajar ini tergolong ke dalam kategori tinggi ditandai dengan kemampuan siswa dalam menuliskan ide pokok sebesar 78% dan dengan persentasi hasil postes siswa sebesar 71% . Pengolahan bahan ajar ini hendaknya dikembangkan pada materi lain dan adanya penelitian lanjutan dengan mengembangkan bahan ajar ini ke dalam bentuk buku ajar, hand-out, atau jenis bahan ajar lainnya secara lengkap. Kata Kunci: Efektivitas Bahan Ajar, Sifat-sifat Periodik Unsur, Empat Tahap Pengolahan Bahan Ajar, Bahan Ajar Mandiri.